Global pattern of the ionospheric response to solar wind variability - Borries, Claudia; Iochem, Pelin (2024)
Recently, a persistent solar wind impact on the variability of the high latitude ionosphere has been reported for the Tromsø station. Since the electrodynamic processes in high latitudes impact the ionosphere and thermosphere conditions globally, the solar wind forcing is part of the variability of the global ionospheric electron density. This can be shown by correlation analyses performed between the Kan-Lee merging electric field (a solar wind – magnetosphere coupling function) and the Total Electron Content obtained from the IGS maps. We present correlation results for a high solar for an example day in 2013, a year of high solar activity during 24th solar cycle. The global patterns of the persistent solar wind impact on the ionosphere vary with geomagnetic latitude, season and local time. These patterns agree well with the typical ionospheric storm climatology. Our results show that the solar wind variability is a relevant parameter to consider for the modelling of TEC.